Nitrification inhibitor and management of liquid hog manure: the effect on soil mineral nitrogen dynamics and wheat yield - Marlo Adriano Bison Pinto; Claudir José Basso; Janine Diéle Feltes; Dionei Schmidt Muraro; Stefen Barbosa Pujol (Semina: Ciências Agrárias, 2023)
Management is of fundamental importance in increasing the efficiency of liquid hog manure (LHM) when used as a source of nitrogen (N) and minimizing its impact on the environment. This paper evaluates the effect of surface application and injection of LHM and the use of dicyandiamide (DCD) on the dynamics of mineral N in the soil and on the components of yield in wheat crops. An experiment was conducted at the Federal University of Santa Maria, Frederico Westphalen Campus, Rio Grande do Sul state, Brazil, involving the following treatments: T0 - Control; T1 - surface application of LHM (Sup); T2 - subsurface injection of LHM (Inj); T3 - surface application of LHM + DCD (Sup+DCD); T4 - subsurface injection of LHM + DCD (Inj+DCD), and T5 - application of N, phosphorus (P), and potassium (K) in mineral form (NPK) in 2014 and 2015. The mineral N recovered with the injection of LHM was superior to surface application, and DSD reduced the speed with which anionic forms of mineral N appear. There was a greater increase in the number of ears of wheat with LHM injection. In 2014, the number of grains per ear was higher with the injection of LHM + DCD, whereas in 2015 all the treatments were higher than the control. There was no difference in 1,000-grain weight between treatments with LHM. Hectoliter weight was higher with the injection of LHM + DCD and the yields observed in this treatment were also higher, not differing from mineral fertilization. It is concluded that LHM injection provides lower losses of N and DCD and reduces the speed with which anionic forms of mineral N appear. In addition, the final yield of wheat grains does not differ when comparing LHM + DCD with mineral fertilization.